Involvement of HB-EGF/Ascl1/Lin28a Genes in Dedifferentiation of Adult Mammalian Müller Glia - Stanchfield, Megan L.; Webster, Sarah E.; Webster, Mark K.; Linn, Cindy L. (Frontiers in Molecular Biosciences, 2020)
Previous studies from this lab have determined that dedifferentiation of Müller glia occurs after eye drop application of an α7 nicotinic acetylcholine receptor (nAChR) agonist, PNU-282987, to the adult rodent eye. PNU-282987 acts on α7 nAChRs on retinal pigment epithelial cells to stimulate production of Müller-derived progenitor cells (MDPCs) and ultimately lead to neurogenesis. This current study was designed to test the hypothesis that the activation of genes involved in the HB-EGF/Ascl1/Lin28a signaling pathway in Müller glia leads to the genesis of MDPCs. RNA-seq was performed on a Müller glial cell line (rMC-1) following contact with supernatant collected from a retinal pigment epithelial (RPE) cell line treated with PNU-282987. Differentially regulated genes were compared with published literature of Müller glia dedifferentiation that occurs in lower vertebrate regeneration and early mammalian development. HB-EGF was significantly up-regulated by 8 hours and expression increased through 12 hours. By 48 hours, up-regulation of Ascl1 and Lin28a was observed, two genes known to be rapidly induced in dedifferentiating zebrafish Müller glia. Up-regulation of other genes known to be involved in mammalian development and zebrafish regeneration were also observed, as well as down-regulation of some factors necessary for Müller glia cell identity. RNA-seq results were verified using qRT-PCR. Using immunocytochemistry, the presence of markers associated with MDCP identity, Otx2, Nestin, and Vsx2, were found to be expressed in the 48 hour treatment group cultures. This study is novel in its demonstration that Müller glia in adult rodents can be induced into regenerative activity by stimulating genes involved in the HB-EGF/Ascl1/Lin28a pathway that leads to MDPCs after introducing conditioned media from PNU-282987 treated RPE. This study furthers our understanding of the mechanism by which Müller glia dedifferentiate in response to PNU-282987 in the adult mammalian retina.